LOW PRESSURE CH2Cl2 PLASMA DISCHARGE (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Glow discharge of dichloromethane (DCM) was investigated employing Optical Emission Spectroscopy (OES), while the electron temperature and electron density were measured using a double Langmuir probe. Deposits formed were characterized by Scanning Electron Microscopy (SEM), X-ray Photo Fluorescence Spectroscopy (XPS) and Fourier Transform Infrared Spectroscopy (FTIR). The species identified by OES were the molecular bands of C2, C3, CH, H2, CH+, HCl+, Cl and C+. The material deposited displays a growing behavior. SEM observation shows several features which correspond to coalesce and growth mechanism. The characterization of the material deposited can explain the different stages of deposits that are formed on the electrode surface. Several factors are concerned in the complexity of the process, regarding the interaction of species formed during the plasma discharge. Involving several bonds types such as: C=C, C=C-CH2-Cl, C-C and CH.